2012
DOI: 10.1007/s00280-012-1951-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of elisidepsin (PM02734) in patients with advanced solid tumors

Abstract: Elisidepsin is well tolerated with predictable reversible transaminase increases. Encouraging preliminary evidence of antitumor activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…reported that acquired resistance to elisidepsin in cancer cells is associated with a switch to the epithelial‐mesenchymal transition (EMT) state, which may be seen as a hallmark of cancer progression to the invasive and metastatic disease . This compound displayed in vivo anticancer activity against human melanoma, liver, pancreas, breast, and prostate cancer xenografts …”
Section: Mollusk‐derived Anticancer Agentssupporting
confidence: 63%
“…reported that acquired resistance to elisidepsin in cancer cells is associated with a switch to the epithelial‐mesenchymal transition (EMT) state, which may be seen as a hallmark of cancer progression to the invasive and metastatic disease . This compound displayed in vivo anticancer activity against human melanoma, liver, pancreas, breast, and prostate cancer xenografts …”
Section: Mollusk‐derived Anticancer Agentssupporting
confidence: 63%
“…It showed promising results for further clinical studies of cancer therapy. Some clinical trials were submitted, including a study of elisidepsin in patients with advanced solid tumors [ 57 ]. The anticancer cyclic depsipeptide plitidepsin was isolated from the Mediterranean tunicate Aplidium albicans [ 58 ].…”
Section: Natural Cyclic Peptides and Analogues In Clinical Trialsmentioning
confidence: 99%
“…These results were promising and gave a rational basis for further investigations such as clinical studies of cancer treatment. A few clinical trials were submitted, they were the study of elisidepsin in patients with advanced solid tumor [ 184 ] and the study of combination therapy with erlotinib in patients with advanced malignant solid tumors. The two studies have been completed and the pharmaceutical company decided to suspend the development of elisidepsin in 2012 in view of commercial unviability of this product.…”
Section: Marine Peptide Products In Market and Clinical Trialsmentioning
confidence: 99%